Beyond the Literal: Refining Text Typology through the Lens of Denotation and Connotation - Testa, Martin (2024)
Text typology, a focal area of text linguistics since the 1970s, still faces a fragmented landscape with diverse typologies each analysing distinct parameters. Although some approaches (particularly those by Werlich and Sabatini) have yielded significant insights, they often fall short in identifying specific text types like irony, humour and metaphors – these texts, while superficially resembling other texts, possess inherent semantic characteristics. This article introduces a novel approach by positioning a denotative/connotative semantic parameter at the top of the typological hierarchy. Beginning with a critical overview of current text typologies, the article justifies the inclusion of such a parameter with references to speech act theory, poetic language and the general theory of verbal humour based on script opposition. Integrated with other surface-level parameters, this model may help effectively classify a broad spectrum of text genres, in the light of contemporary linguistic theories.
Keywords: text linguistics; text types; text typology; textual sign; denotation and connotation; irony and humour